Kierunki zmian ubezpieczeń społecznych rolników - Walczak, Damian (The Directions of Changes in Farmers' Social Insurance, 2008)
The first possibility of receiving pension appeared for farmers wishing to finish work on their own farmlands in the post-war period in 1962. The only condition was to assign the farm property ownership to the State. Afterwards, the law was changed repeatedly, but the condition of transferring the ownership was still valid. For that reason, the popularity of such a solution remained rather low. Since 1st January 1978 farmers had been incorporated into a social insurance system. These changes made farmers pay social insurance contributions in return for the right to receive pension payments or benefits in case of incapacity to work. The present law regulation introduced on 20th December 1990 needs amendments. One of the reasons is the amount of government grants which are donated to the farmers' insurance system. It accounts for app. 90% of all system expenses. The second reason is the range of pension payments depending on a farmer's income.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 444-449